Penerapan lean manufacturing dalam mereduksi pemborosan pada raw material bumbu dengan metode PDCA - Reka Firwayani Wigati; Devi Maulida Rahmah; Irfan Ardiansah; Totok Pujianto (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
PT. XYZ is a manufacturing company that produces processed food. Instant noodles is one of the type product that produced by PT. XYZ, which contains raw material for spice as one of the main complementary material. This research focused on the waste of raw material for instant noodles seasoning. The purpose of this research is to reduce the waste and to determine which factors that cause waste. This study using Plan Do Check Action method which is expected to reduce waste that occurs within the company. The highest waste within 18 days of production was 15.28%, the lowest was -2.3% and there was no waste, and the average waste during that period was 3.2%. the result of the highest and dominant factor in the waste of raw material was the lack of skill of the operator was just moved from screw division, thus they didn’t know how to operate machine. While the second factor was the lack of maintenance of the machine by quality control departement for pitch standardization. And the third factor was the cutter knife didn’t really cut because of the cutter block.